FACTORS AFFECTING FIRM VALUE IN THE CONSUMER NON-CYCLICAL SECTOR IN INDONESIA - Suryanata, Sherina; Susanto, Liana (International Journal of Application on Economics and Business, 2025)
The study aims for empirical evidence about the effect of firm size, liquidity, leverage, profitability, and listing age on firm value in consumer non-cyclical companies in the Indonesia Stock Exchange for 2019-2021.Company size (SIZE) in this study is measured by the natural logarithm of total assets. Profitability in this research is measured by Return on Assets (ROA) which is calculated by dividing net profit after tax by total assets. Liquidity in this study is measured by the Current Ratio (CR) which is calculated by dividing total current assets by total short-term liabilities. Leverage in this study is measured by the Debt to Equity ratio (DER) which is calculated by dividing total liabilities by total equity. Listing age (AGE) in this study is calculated by subtracting the year of research from the year the company conducted the year of the company's IPO. The total sample for this research was 47 companies, where the sample was selected using a purposive sampling method. This research data was analyzed using multiple linear regression analysis techniques processed with SPSS 25.0. The results of this research show that profitability has a significant positive influence on company value. Meanwhile company size, liquidity, leverage, and listing age do not have a significant influence on company value.